EVALUASI KINERJA PENGAWAS SMA DI KABUPATEN BENGKULU TENGAH, PROVINSI BENGKULU - Iswadi Idris (PAKAR Pendidikan, 2015)
The objective of study is to find out the performance of senior high school supervisors in central Bengkuluregency Bengkulu province that consists of: (1) composing supervisory planning, (2) carrying out the supervisory planning, (3) evaluating the implementation of the supervisory planning, and (4) guiding and training of professional teachers and school principals. The research was conducted in regencies and cities in central Bengkulu regency Bengkulu province. The subject of research is senior high school supervisor in central Bengkulu regency Bengkulu province (34 persons). The method of research is mixed method. The research design used Provus is Descrepancy Evaluation Models (DEM). The data were colected by using observation, interview, questionnaire and documents. The results of research shows that: (1) the performance of supervisors in composing planningsis good category, (2) the performance of supervisors in carrying out sepervisory planningis fair category, (3) the performance of supervisors in evalauating the product of implementation of the supervisory planning is fair category, and (4) the performance of supervisors in guiding and training of professional teachers or school principals in central Bengkulu regency Bengkulu province is poor category.